Association Between Body Mass Index and All-Cause Mortality in a Prospective Cohort of Southern Chinese Adults Without Morbid Obesity - Hu, Feng; Cheng, Jianduan; Yu, Yun; Wang, Tao; Zhou, Wei; Yu, Chao; Zhu, Lingjuan; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Physiology, 2022)
Objective: This prospective study examined the relationship between body mass index (BMI) and all-cause mortality in Chinese adults without morbid obesity. Methods: We prospectively examined the relationship between BMI and all-cause mortality in 12,608 Southern Chinese adults with age ≥35 years who participated in the National Key R&D Program from 2013-2014 to 2019-2020. Cox proportional hazards models were used to examine the association between BMI and all-cause mortality. Results: The prevalence of being underweight, normal weight, overweight and having moderate obesity was 7.36%, 55.83%, 28.51% and 8.31%, respectively. A total of 683 (5.65%) deaths occurred during a median follow-up period of 5.61 years. The Cox proportional hazards models indicated that a continuous BMI level was negatively associated with all-cause mortality [adjusted-hazard ratio (HR) per 1 kg/m2 increase: 0.96, 95% CI 0.93 to 0.98, P <0.001]. Furthermore, the HRs of all-cause mortality in the underweight, overweight and moderate obesity groups were 1.31 (1.05, 1.64), 0.89 (0.73, 1.08) and 0.64 (0.44, 0.92), respectively in the confounder model relative to the normal weight group. Survival analysis further confirmed this inverse association of the four BMI categories with mortality. Conclusions: BMI was negatively associated with all-cause mortality in southern Chinese adults without morbid obesity. Compared to the normal weight category, adults in the moderate obesity category had lower all-cause mortality, whereas being underweight was associated with increased all-cause mortality.